ACTIVITY RATIO ANALYSIS TO ASSESS THE FINANCIAL PERFORMANCE OF PT INDUSTRI JAMU AND FARMASI SIDOMUNCUL TBK - Cut Rozana Sari; Irada Sinta; Zuriani; Mohd. Heikal; Rico Nur Ilham (PT. Radja Intercontinental Publishing, 2024)
Activity Ratio Analysis to Assess Financial Performance in the herbal medicine and pharmaceutical industry sidomuncul Tbk which is listed on the Indonesian Stock Exchange (BEI). Financial report analysis is needed by companies to assess company performance and compare the company's condition from the previous year. One of the ratios used in conducting analysis is the activity ratio. The activity ratio is useful for analyzing the use of existing resources and to support company activities. There are several types of activity ratios that are used as measuring tools to determine a company's ability to use its assets, namely total asset turnover, working capital turnover, fixed asset turnover, inventory turnover, and accounts receivable turnover. Based on the results of calculating the activity ratio at PT. Tbk's herbal medicine and pharmaceutical industry in 2021 to 2022 shows that this company experience significant change _ in performance his activities related investment in operational . However, the results achieved are still below industry standards, which shows that the company's performance is still not good compared to other similar industries. This needs to be a company's vigilance to always improve performance and have high competitiveness .